2011
DOI: 10.1021/jp109686n
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Induced Structural Transitions of a 1,3,5-Tris(10-ethoxycarbonyldecyloxy)benzene Assembly Revealed by Scanning Tunneling Microscopy

Abstract: The effect of solvent on a two-dimensional (2D) self-assembly of 1,3,5-tris(10-ethoxycarbonyldecyloxy)benzene (TECDB) has been systematically investigated by scanning tunneling microscopy. Through careful investigation of the solvent effect on molecular self-assembly, the solution concentration is also found to be a factor in assembly formation and transition. The same self-assembled structure is obtained using 1-phenyloctane, 1-octanol, n-tridecane, and n-tetradecane as a solvent under high solution concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…10 In particular, by confining the selfassembly process on solid substrates, two-dimensional (2D) structures can be formed 11,12 by exploiting a number of different intermolecular forces: from metal coordination 13,14 to hydrogen bonding 14,15 , to weaker dispersion interactions. 16 While the nature of the interactions between the molecular units is typically the key factor in determining the resulting assembly, other more subtle influences have also been reported to affect the final supramolecular structures: the chemistry and symmetry of the substrate (even for inert surfaces such as highly ordered pyrolytic graphite (HOPG) and Au(111) 17 ), the temperature, [18][19][20] the ultra-high vacuum (UHV) or solution environment, 19,21,22 the nature of the solvent, 19,[23][24][25][26][27][28] the concentration of the solute (the self-assembling molecule), 18,[29][30][31][32][33][34][35] and any co-adsorption of solvent or guest molecules 24,25,34,36,37 . The possibility of controlling supramolecular polymorphism by weak intermolecular interactions, such as interactions with the solvent, is a new and fascinating approach to the ultimate goal of rationally programming molecular self-assembly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In particular, by confining the selfassembly process on solid substrates, two-dimensional (2D) structures can be formed 11,12 by exploiting a number of different intermolecular forces: from metal coordination 13,14 to hydrogen bonding 14,15 , to weaker dispersion interactions. 16 While the nature of the interactions between the molecular units is typically the key factor in determining the resulting assembly, other more subtle influences have also been reported to affect the final supramolecular structures: the chemistry and symmetry of the substrate (even for inert surfaces such as highly ordered pyrolytic graphite (HOPG) and Au(111) 17 ), the temperature, [18][19][20] the ultra-high vacuum (UHV) or solution environment, 19,21,22 the nature of the solvent, 19,[23][24][25][26][27][28] the concentration of the solute (the self-assembling molecule), 18,[29][30][31][32][33][34][35] and any co-adsorption of solvent or guest molecules 24,25,34,36,37 . The possibility of controlling supramolecular polymorphism by weak intermolecular interactions, such as interactions with the solvent, is a new and fascinating approach to the ultimate goal of rationally programming molecular self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of controlling supramolecular polymorphism by weak intermolecular interactions, such as interactions with the solvent, is a new and fascinating approach to the ultimate goal of rationally programming molecular self-assembly. However, its fundamental mechanisms are still not clearly understood, and it is likely that multiple mechanisms may be simultaneously at play: from co-adsorption of solvent and guest molecules 25,31 to different solvation of small molecular aggregates precursors to the extended self-assembly in different solvents. 23 In this work, we investigate the combined effects of the molecular structure and the nature of solvent in the molecular self-assembly of benzene dicarboxylic acids at the liquid/solid (HOPG) interface.…”
Section: Introductionmentioning
confidence: 99%
“…23 Alkanes employed as low volatility solvents for monolayer preparation at liquid/solid interfaces are often co-adsorbed too in self-assembled monolayers of alkyl-substituted aromatic molecules forming multi-component network structures. [24][25][26] Therefore we conjectured that the intermolecular alkyl chain interdigitations between pairs of alkyl chains of adjacent molecules of a DBA derivative could be blocked efficiently by incorporation of a straight-chain alkane molecule into the alkyl chain pair, leading to the formation of a trigonal DBA-OCn-alkane complex ( Figure 2). Tiling of this trigonal complex is intriguing, because it should result in the formation of porous trigonal star (t-star), hexagonal, and hexagonal star (h-star) structures of p3, p6, or p6 symmetry, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…play important roles as well. Up till now, many researches reported that the self‐assembly structures could be greatly affected by the solution concentration . The characterization was performed when the solvent evaporated completely as well …”
Section: Introductionmentioning
confidence: 99%